MODEL LAB SITE PLS MELALUI PELEMBAGAAN RUMAH PINTAR BU EEN - Komar, Oong (Universitas Pendidikan Indonesia, 2016)
This study was based-backs SCTV findings regarding the phenomenal figure of Mrs. Een Sukaesih as inspirational women in the learning of the children and the community built around that by SCTV was awarded the Special Awards category of education, dedication to the community and humanity. With the assistance of assistance by the department (laboratory) facilities design by PLS embodies the children's learning and community development are packed with smart home albarokah name, and has five program activity centers. The formulation of the research problem: (1) whether the exploration results in Rumpin Albarokah there is a vision, mission, goals, objectives and programs and their conformity with the realization? (2) whether the results of the analysis are Rumpin Albarokah delegation, leadership and familiarization program implementation strategy? (3) How do find / labsite PLS models prove effective in enhancing the competence of students on community empowerment through Andragogy approach? Qualitative research approach with data collection techniques interview, observation and document and using processing techniques and data analysis with data reduction, data display and verification. This study places in Rumpin Albarokah Sumedang, West Java. The results show Rumpin are: (1) tools for community empowerment that embodies the activity of children, youth, and elderly women, (2) facilitate learning and empowerment, (3) prove the model lab site PLS is effective in enhancing the competence of students on community empowerment through approach Andragogy ,